Socio-demographic and Healthcare-seeking Predictors of Undernutrition among Children Under-five Years of Age in a Western District of Nepal - Paudel, Rajan; Gurung, Yogendra Bahadur; Poudyal, Amod Kumar; Khatri, Bijay; Bhatta, Deepak Raj; Acharya, Dilaram; Singh, Jitendra Kumar; Adhikari, Min Raj; Sapkota, Ranjan; Mahotra, Narayan Bahadur; Upadhyaya, Dipak Prasad (Journal of Nepal Health Research Council, 2020)
Background: Undernutrition is highly prevalent in Nepal, which interferes with physical and mental development among children. It is one of the severe health problems contributing to the significant portion of the disease burden. This study aimed to explore socio-demographic and healthcare-seeking related predictors of undernutrition among children under five years old in Dang, Nepal. Methods: This was a descriptive cross-sectional study. A sample of 426 children was participated through stratified proportionate random sampling to identify socio-demographics and healthcare-seeking predictors of undernutrition. Multivariable regression was applied to identify the independent predictors of undernutrition. Results: This study found that children below 24 months of age were more likely to be undernourished than children aged 24-36 months. Female children (OR=2.32, 95% CI: 1.19-4.54), illiterate or non-formally educated women (OR=4.09, 95% CI: 1.84-9.08), mother’s occupation other than a housewife (OR=13.05, 95% CI: 4.19-40.68), labor work of father (OR=2.40, 95% CI: 1.04-5.57) had increased risk of undernutrition among children. Similarly, food insufficiency from their land, antenatal care visit, postnatal care visit, and delivery place were significantly associated with childhood undernutrition among children. Conclusions: The study showed that undernutrition among children is associated with age and gender of children, educational attainment of the mother, food sufficiency, health-seeking practices of the mother during pregnancy, delivery, and postnatal. Socio-demographics and health-seeking practices related predictors must be explicitly considered to address undernutrition among children under the age of five years. Keywords: Children; health care seeking; Nepal; socio-demographic factors; undernutrition.